Vocal Variability Post Swallowing in Individuals with and without Oropharyngeal Dysphagia - Santos,Karoline Weber dos (2015)
Introduction Voice modification after swallowing may indicate changes in the transit of the bolus. Objective The aim of this study is to verify the use of perceptual voice analysis to detect oropharyngeal dysphagia. Study Design Case series. Methods Twenty-seven patients with dysphagia as diagnosed by videofluoroscopy and 25 without were evaluated. The sustained vowel /a/ was recorded before this exam and after swallowing different consistencies (pasty, liquid and solid). For the voice evaluation, the GRBAS scale (grade, roughness, breathiness, asthenia and strain) and the parameter "wet voice" were used. Three judges blinded to study group and time of emission performed voice analysis. Results Individuals with dysphagia showed significant decrease in grade of voice and asthenia and increase in strain after swallowing pasty substances, differing from individuals without dysphagia who showed no modification of the parameters after swallowing. The wet voice parameter showed no difference after swallowing in both study groups. Conclusion The decrease in grade and asthenia and increased strain are indicative of a swallowing disorder, indicating increased vocal strain to clean the vocal tract of food. The modification of vocal production after swallowing proved to be a trusted resource for detection of swallowing disorders.